EFEKTIFAS EDUKASI DALAM PENCEGAHAN DIABETES MELITUS DI DESA GENENG POLOKARTO SUKOHARJO - Rahmasari, Ikrima; AM, Ady Irawan; Luthfiyanti, Niken; Purwaningsih, Iswanti (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2023)
Background: Diabetes Mellitus (DM) is a metabolic syndrome due to impaired quantity and function of insulin which causes high blood glucose levels (hyperglycemia). Early prevention needs to be done for early detection of chronic diseases such as DM which have good risk factors due to unhealthy lifestyles and heredity. Early detection of DM can be done through screening by checking blood sugar levels at the time. In addition, success in preventing the onset of DM and controlling blood sugar levels in people with DM depends on people's behavior. Changes in behavior towards a healthy lifestyle in the context of correct DM prevention and control will be realized if the community has sufficient knowledge about DM and its prevention. The purpose of this activity is to add health information to the public about education on the prevention of Diabetes Mellitus. The method is carried out by lectures, discussions and questions and answers while the media uses leaflets. The education delivered increases public knowledge about diabetes risk prevention education, so that people can independently prevent the risk of diabetes mellitus which is a degenerative disease and is predicted to increase every year.